Rancangan Game Edukasi Bahasa Arab Untuk Murid Taman Kanak Kanak Berbasis Augmented Reality - Mukmin, Muhammad; Hamsinar, Henny; Fadillah Jasir, Sitti Nur (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2025)
Early childhood education aims to equip preschool learners with foundational social, emotional, cognitive, and linguistic abilities through engaging instructional activities adapted to developmental stages. However, learning practices in several institutions remain traditional, relying on textbooks, verbal instruction, and static visual aids without the support of interactive technology. This condition is also found at TK Islam Al-Amanah, particularly in introducing Arabic vocabulary, where instruction is still dominated by demonstration and question–answer methods, resulting in limited learner interaction. This study aims to design an educational game based on Augmented Reality (AR) as a learning medium for introducing Arabic vocabulary related to everyday objects among kindergarten learners. The development method employed was the Multimedia Development Life Cycle (MDLC), consisting of concept, design, material collection, assembly, testing, and distribution. The resulting application, called Arabica, provides three-dimensional object visualization through AR markers, Arabic vocabulary pronunciation through a learning menu, and a picture-guessing game to enhance learner engagement. In its implementation, teachers act as facilitators by helping children position the camera toward the marker and guiding pronunciation, while learners interact directly with virtual objects and audio outputs. The development results indicate that Arabica supports visual and interactive material delivery and assists learners in understanding and memorizing Arabic vocabulary in a more enjoyable manner.